Fire characteristics of steel members coated with nano‐enhanced polymers. (25th January 2013) - Butler, Kathryn M.; Cheng, Alexander H.‐D.; Mullen, Christopher; Al‐Ostaz, Ahmed
ABSTRACT Polymeric coatings applied to masonry infill walls have been demonstrated to provide protection against blast. Steel frames may be embedded in these walls to improve the structural characteristics of the building. During the process of retrofitting the walls with blast protection polymeric coatings, the steel frame may be fully or partially coated with these materials to provide adequate anchorage of the retrofit system to the frame and to avoid global failure of walls subjected to blast loading. The development of a blast‐resistant coating for masonry walls that safeguards all structural elements in a fire would provide buildings with protection against explosions and a fire following the blast, as well as against ordinary building fires. This paper uses a numerical tool based on the particle finite element method to evaluate the melting and dripping of nano‐enhanced polymeric coatings applied on steel members embedded within masonry walls. Viscosity measurements were performed to obtain needed parameters for the simulations. Polyurea nanocomposite residues showed a minimum in viscosity with temperature, possibly caused by cross‐linking and charring. Model results for the polyurea residue with the lowest value of minimum viscosity showed that the coating remained attached, although there was some flow that caused a chunk of material to break off from an overhang. Copyright © 2013 John Wiley & Sons, Ltd.